2001
DOI: 10.1074/jbc.m011785200
|View full text |Cite
|
Sign up to set email alerts
|

The Uptake Inhibitors Cocaine and Benztropine Differentially Alter the Conformation of the Human Dopamine Transporter

Abstract: The inhibitor benztropine was unique in its inability to protect Cys-135. Moreover, whereas cocaine, WIN, mazindol, and dopamine enhanced the reaction of Cys-90 with MTSET, benztropine had no effect on this reaction. These two features combine to give benztropine its weak potency in protecting ligand binding to wild-type DAT from MTSET. These results indicate that different inhibitors of DAT, such as cocaine and benztropine, produce different conformational changes in the transporter. There are differences in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
110
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(118 citation statements)
references
References 31 publications
8
110
0
Order By: Relevance
“…This cysteine was also protected from reaction when cocaine was present, consistent with a model in which cocaine stabilizes an outward facing conformation of DAT (58). This dynamic rearrangement is underscored by our findings that cocaine is not a neutral blocker but rather alters the conformation of extracellular and intracellular cysteines in DAT (59,60). That cocaine binding is greatly enhanced by sodium (61) is also consistent with cocaine binding preferentially to a C2-or C3-like configuration.…”
Section: Table 1 Tyrosine Kinetics Of Tyt1 Variantssupporting
confidence: 72%
“…This cysteine was also protected from reaction when cocaine was present, consistent with a model in which cocaine stabilizes an outward facing conformation of DAT (58). This dynamic rearrangement is underscored by our findings that cocaine is not a neutral blocker but rather alters the conformation of extracellular and intracellular cysteines in DAT (59,60). That cocaine binding is greatly enhanced by sodium (61) is also consistent with cocaine binding preferentially to a C2-or C3-like configuration.…”
Section: Table 1 Tyrosine Kinetics Of Tyt1 Variantssupporting
confidence: 72%
“…Newman and colleagues have identified dissimilarities between benztropine and cocaine actions at the DAT via distinctive structureactivity relationship profiles (Newman and Kulkarni, 2002). In addition, benztropine altered the accessibility of alkylation agents to wild-type DAT cysteine residues in a pattern distinct from the pattern generated by cocaine, WIN 35,428, and mazindol (Reith et al, 2001). The latter study demonstrated a primary alkylation pattern difference at C90, a DAT extracellular loop cysteine residue that immediately follows TM 1.…”
Section: Discussionmentioning
confidence: 86%
“…Furthermore, BZT analogs are less effective than cocaine in maintaining high rates of responding in self-administration procedures (Woolverton et al, 2001). These findings suggest differences between these drugs and cocaine analogs in their interactions with the DA transporter (Vaughan et al, 1999;Reith et al, 2001;Chen et al, 2004), which may be responsible for the diminished cocaine-like pharmacological activity of the BZT analogs.…”
mentioning
confidence: 72%